Method of amended soils for compressed block and mortar in earthen construction - Admassu, Kassahun (Zede Journal of Ethiopian Engineers and Architects, 2023)
The paper presents the results of a research conducted aiming at developing a method of producing building block and mortar from locally available natural soils and earth minerals. The main focus of the effort is to establish or advance wall making building blocks and jointing/binding mortars from amended soils with cementitious raw lime/nonfactory manufactured and pozzolanic minerals. The targeted beneficiaries of the success are the over eighty million disadvantaged Ethiopians residing in the rural and semi-rural areas of the country. They deserve a decent, sustainable, ecofriendly and a popular technology based habitat. The long journey towards achieving the noble goal was initiated by investigating the suitability of soils and earth minerals, preparation and testing of informative specimens and the production of mortar cubes and proto-type building blocks in their actual size to simulate field application conditions. The specifics of this particular move is thoroughly focusing on the two prime parameters of compressive strength and durability (water resistance) which are the determinant factors for the viable application of earth based wall making in puts. The attained results of the effort indicated that the designed mix proportioning of the ingredients confirmed that the products are acceptable both in compressive strength and durability terms for the intended purpose. To this effect, the blocks produced using the proposed method, are named as amended compressed earth blocks (ACEBs).